VODP's experience capitalization journey - Wanyoto, Anthony (Technical Centre for Agricultural and Rural Cooperation, 2019)
To build on the achievements of the Vegetable Oil Development Project in Uganda, different experience capitalization trainings and workshops are being held with staff and stakeholders of a follow up project - the National Oil Palm Project (NOPP). It is anticipated that the capitalization process will help strengthen the monitoring and evaluation component at NOPP, and help bring about change in the agriculture sector more widely.